2017
DOI: 10.1017/s2040174417000617
|View full text |Cite
|
Sign up to set email alerts
|

Exercise during pregnancy and its impact on mothers and offspring in humans and mice

Abstract: Exercise during pregnancy has beneficial effects on maternal and offspring's health in humans and mice. The underlying mechanisms remain unclear. This comparative study aimed to determine the long-term effects of an exercise program on metabolism, weight gain, body composition and changes in hormones [insulin, leptin, brain-derived neurotrophic factor (BDNF)]. Pregnant women (n=34) and mouse dams (n=44) were subjected to an exercise program compared with matched controls (period I). Follow-up in the offspring … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
34
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 71 publications
1
34
0
Order By: Relevance
“…However, with regard to long-term effects, the offspring of exercising mouse dams had significantly lower fat mass and leptin levels than controls. Furthermore, serum BDNF levels were elevated three-fold in the exercise offspring group compared with control [109]. In summary, this shows that lifestyle factors, especially regular physical activity, can shape the metabolic profile of children in the long term.…”
Section: Early-life Programming and The Influence Of Different Adipokmentioning
confidence: 72%
See 1 more Smart Citation
“…However, with regard to long-term effects, the offspring of exercising mouse dams had significantly lower fat mass and leptin levels than controls. Furthermore, serum BDNF levels were elevated three-fold in the exercise offspring group compared with control [109]. In summary, this shows that lifestyle factors, especially regular physical activity, can shape the metabolic profile of children in the long term.…”
Section: Early-life Programming and The Influence Of Different Adipokmentioning
confidence: 72%
“…In a comparative study, we analyzed the long-term effects of an exercise program during pregnancy on metabolism, weight gain, body composition, and changes in leptin and BDNF [109]. Human and animal models were synchronized according to study design, age, and serum parameters.…”
Section: Early-life Programming and The Influence Of Different Adipokmentioning
confidence: 99%
“…Human and animal studies have shown that environmental stimuli, such as maternal physical activity, influence the brain development and function of both mother and offspring. [1][2][3] In humans, infants from active mothers during pregnancy (three times per week, at least 20 min/day at 55% of their maximal aerobic capacity) showed a better response to sound discrimination and auditory memory as measured by electroencephalography. 2 In rats, young pups born from dams which were active throughout pregnancy showed an increased amount of neuronal and non-neuronal cells in the hippocampus, improved cognitive functions (habituation behaviour and spatial learning) and enhanced memory as tested using a novel object recognition paradigm.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, a recent study has demonstrated that exercise during pregnancy did not change BDNF levels in brain of mice offspring at 21 days old. 3 Absence of gene expression modulation in the foetus' brains could be related to technical difficulties, as the whole brain, and not specific regions, were analysed, due to the foetus' brain small size. Alternatively, it is possible that the underlying mechanism to improve neuroplasticity in foetus from exercised mothers possibly is not related to changes in neurotrophic gene expression.…”
mentioning
confidence: 99%
“…12 The importance of a public health approach is underlined by the growing knowledge of gene-environment interaction, respectively epigenetics providing the key to transform the genetic information into phenotype over generations. 13 Therefore effective health promotion should involve all actors from different sectors:…”
mentioning
confidence: 99%